f(x) = ax + b - forma generala;
f(-1)= -a + b = 3;
f(2)= 2a + b = -1;
formam un sistem
[tex] \left \{ {{-a+b=3} \atop {2a+b=-1}} \right. [/tex]
inmultim prima relatie cu 2
[tex]\left \{ {{-2a+2b=6} \atop {2a+b=-1}} \right.[/tex]
si adunam cele doua relatii
-2a cu 2a se reduce si ne ramane
3b=5
b=[tex] \frac{5}{3} [/tex]
-a + b = 3
-a + [tex] \frac{5}{3} [/tex] = 3
-a = 3 - [tex] \frac{5}{3} [/tex]
- a=[tex] \frac{9}{3} [/tex] - [tex] \frac{5}{3} [/tex]
- a = [tex] \frac{4}{3} [/tex]
a = - [tex] \frac{4}{3} [/tex]